Novel direct sequence spread spectrum communication method - Fanglin GU; Jinlin PENG; Yuzhen HUANG; Shengqun CAO; Haitao ZHAO; Jibo WEI (Tongxin xuebao)
In response to the problem of limited performance and low spectral efficiency in complex multipath environments of traditional direct sequence spread spectrum communication, a cyclic prefix (CP) block transmission structure spread spectrum system with a time-frequency hybrid direct sequence spread spectrum receiver structure was proposed.The system adopted maximum ratio combination (MRC) in the frequency domain to achieve equalization and de-spreading processes simultaneously, while achieving optimal reception performance and omitting the IFFT process to reduce computational complexity significantly.On this basis, it was proposed to replace the m-sequence with the constant amplitude zero auto correlation (CAZAC) sequence as the spread spectrum sequence, which significantly improved the system performance without increasing computational complexity.Finally, a high-speed spread spectrum communication method based on cyclic code shift keying (CCSK) was proposed to solve the problems of low spectrum utilization efficiency and limited transmission rate in traditional direct sequence spread spectrum.By utilizing the property of Fourier transform time-domain cyclic shift, a low implementation complexity CCSK decoding method was designed, which reduced the multiplication number required for CCSK de-spreading by O(N2) reduced to O (Nlog N), greatly reducing resource consume.The simulation results show that compared to existing direct sequence spread spectrum methods, the proposed method achieves approximately 3 dB gain in both Gaussian and complex multipath channel environments.